La-doped in-situ coexisting fluorite-perovskite high-entropy zirconate ceramic

CN122916657APending Publication Date: 2026-10-16LANZHOU INSTITUTE OF CHEMICAL PHYSICS CHINESE ACADEMY OF SCIENCES
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202611144920.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

虽然上述报道公开了高熵双相材料的存在,但对于双相形成调控的技术手段未做详细说明

Benefits of technology

1、本发明所述高熵锆酸盐陶瓷材料存在立方缺陷萤石相和钙钛矿相两种晶体结构,其中萤石相(A2B2O7)为Fm-3m空间群,由阳离子与8个氧离子形成立方体配位结构,阳离子位于氧离子构成的立方体中心,A、B阳离子随机分布,形成无序的缺陷萤石结构;钙钛矿相(ABO3)为Pm-3m空间群,A位离子与12个氧离子形成立方八面体配位,B位离子与6个氧离子形成氧八面体配位,B-O八面体通过共顶点连接成三维网络,A位离子填充于八面体间隙中,A、B阳离子特定分布,形成有序的钙钛矿结构。有序-无序的双相结构在纳米尺度上紧密耦合,相界处形成了明显的晶格失配及高密度位错缺陷。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122916657A_ABST
    Figure CN122916657A_ABST
Patent Text Reader

Abstract

The present application relates to a kind of La doped in-situ symbiotic fluorite-perovskite high-entropy zirconate ceramic, the chemical general formula of the high-entropy zirconate ceramic is [La x (A y B y ) 1‑y ) 1‑x ]2Zr2O7, wherein A site element is selected from one of Ca, Mg, Sr, B site element is selected from two or more of Fe, Cr, Mn, Co, Ni, and each B site element is composed of equimolar ratio;X is the mole percentage of La element in the total mole amount of La and (A+B) site, and 0 1‑x X 1‑x 0.4;Y is the mole percentage of A element in the total mole amount of (A+B) site, and 0.3 1‑x Y 1‑x 0.5;The high-entropy zirconate ceramic has in-situ symbiotic fluorite and perovskite dual-phase structure of defect, and belongs to cubic system.The high-entropy zirconate ceramic has structural stability, and can be applied in thermal barrier protection, thermal radiation regulation or electromagnetic wave absorption field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of ceramic materials technology, and in particular to a La-doped in-situ symbiotic fluorite-perovskite high-entropy zirconate ceramic. Background Technology

[0002] Zirconate ceramics are widely used in thermal barrier protection due to their low thermal conductivity, good high-temperature phase stability, and high resistance to sintering. Among them, defective fluorite-type zirconate is a material system that has been extensively studied. However, as service temperatures increase further, thermal radiation gradually becomes an important heat transfer mechanism in high-temperature environments. Existing zirconate thermal barrier materials generally suffer from low infrared emissivity, making it difficult for heat on the material surface to be released in a timely manner through radiation, which easily leads to heat accumulation on the material surface and affects the thermal protection effect. Therefore, relying solely on low thermal conductivity to achieve thermal protection is no longer sufficient to meet the requirements of high-temperature environments.

[0003] Perovskite materials are widely used in high-temperature infrared radiation materials due to their high infrared emissivity and rich lattice vibration modes. The infrared radiation performance of perovskite materials can be improved by controlling the cation occupancy in the perovskite structure. However, existing perovskite materials are prone to elemental segregation, phase separation, and structural instability under high-temperature conditions, thus affecting their long-term service stability.

[0004] In recent years, high-entropy ceramics have attracted widespread attention in the field of high-temperature structural and functional materials due to their high-entropy and lattice distortion effects. Introducing multiple equimolar or near-equimolar components can increase the configurational entropy of the material and enhance the degree of local lattice distortion. As the system's dimensional disorder δ increases, the phase structure stability and phase composition of the material may change, leading to a multiphase coexistence structure. Simultaneously, high configurational entropy helps reduce the system's free energy, thereby improving the stability of the multiphase structure. Currently, research has reported high-entropy two-phase ceramic materials, including CN 117902879 A, ​​which discloses a spinel-perovskite two-phase high-entropy ceramic powder material and its preparation method; CN121248277 A, which discloses a spinel-perovskite three-phase high-entropy ceramic powder material; CN 117902890 A, which discloses a spinel-corundum two-phase high-entropy ceramic material and its preparation method; and CN119118661 A, which discloses a low thermal conductivity two-phase high-entropy ceramic material with controllable microstructure. While the aforementioned reports disclosed the existence of high-entropy dual-phase materials, they did not provide detailed explanations of the technical methods for controlling the formation of the dual phases. Furthermore, there are no existing reports on defect fluorite-perovskite dual-phase high-entropy zirconate ceramics and their in-situ co-creation control methods. Summary of the Invention

[0005] The technical problem to be solved by the present invention is to provide a La-doped in-situ symbiotic fluorite-perovskite high-entropy zirconate ceramic with structural stability.

[0006] To address the aforementioned problems, the present invention provides a La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramic, characterized in that: the general chemical formula of the high-entropy zirconate ceramic is [La]. x (A y B 1-y ) 1-x ]2Zr2O7, wherein the A-site element is selected from one of Ca, Mg, and Sr, and the B-site element is selected from two or more of Fe, Cr, Mn, Co, and Ni, and the elements at the B-site are composed in an equimolar ratio; x is the molar percentage of La element in the total molar amount of La and (A+B) sites, and 0 < x < 0.4; y is the molar percentage of A element in the total molar amount of (A+B) sites, and 0.3 ≤ y < 0.5; the high-entropy zirconate ceramic has an in-situ coexisting two-phase structure of defective fluorite and perovskite, and belongs to the cubic crystal system.

[0007] The configurational entropy S of the high-entropy zirconate ceramic config >1.5R, where R is the gas constant.

[0008] The dimensional disorder δ of the high-entropy zirconate ceramic is greater than 5%.

[0009] The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described above includes the following steps: (1) Weigh the raw materials according to the stoichiometric ratio, wherein the La element is derived from La2O3 oxide, the Zr element is derived from ZrO2 oxide, the A-site element is selected from one of CaO, MgO, and SrO, and the B-site element is selected from two or more oxides of Fe2O3, Cr2O3, Mn3O4, Co3O4, and NiO. (2) The raw material from step (1) is mixed with ball milling media and solvent and ball milled. After drying and sieving, a uniformly mixed precursor powder is obtained. (3) After the precursor powder is calcined at high temperature in air, it is cooled and ground to obtain high-entropy zirconate ceramics.

[0010] The conditions for ball milling in step (2) are as follows: a planetary ball mill is used, the ball milling media is zirconia balls, the mass ratio of zirconia balls with a diameter of 1~3mm to zirconia balls with a diameter of 5~10mm is 6:4, the ball milling solvent is deionized water, the ball milling speed is 300~600r / min, the ball milling time is 12~24 hours, and the mass ratio of balls, materials and solvent is (3~5):1:(1~2).

[0011] The drying conditions in step (2) refer to a temperature of 60~80℃ and a time of 6~12 hours.

[0012] The sieving condition in step (2) refers to using a sieve with a mesh size of 100-200.

[0013] The conditions for high-temperature calcination in step (3) are: calcination temperature of 1500~1600℃; the programmed temperature rise is: rise to 1200℃ at a heating rate of 5~10℃ / min, calcination for 4~6 hours; then rise to the target temperature at a heating rate of 2~5℃ / min, calcination time is 12~24 hours.

[0014] In step (3), the cooling method is continuous cooling or isothermal cooling, and the cooling medium is air.

[0015] Compared with the prior art, the present invention has the following advantages: 1. The high-entropy zirconate ceramic material of this invention exhibits two crystal structures: a cubic defect fluorite phase and a perovskite phase. The fluorite phase (A₂B₂O₇) belongs to the Fm-3m space group, with a cubic coordination structure formed by cations and 8 oxygen ions. The cations are located at the center of the cubic oxygen ions, and A and B cations are randomly distributed, forming a disordered defect fluorite structure. The perovskite phase (ABO₃) belongs to the Pm-3m space group, with A-site ions forming cubic octahedral coordination with 12 oxygen ions, and B-site ions forming oxygen octahedral coordination with 6 oxygen ions. The BO octahedra are connected by shared vertices to form a three-dimensional network, with A-site ions filling the interstices of the octahedra. The A and B cations are specifically distributed, forming an ordered perovskite structure. The ordered-disordered dual-phase structure is tightly coupled at the nanoscale, resulting in significant lattice mismatch and high-density dislocation defects at the phase boundaries.

[0016] 2. In the high-entropy zirconate ceramic of this invention, the perovskite phase is formed in situ during sintering due to the segregation of La element. 3+ Its ionic radius (approximately 1.16 Å) is significantly larger than that of alkaline earth metals (such as Ca). 2+ Approximately 1.12 Å) and transition metals (such as Fe) 3+ (Approximately 0.65 Å) When La replaces some A-site ions, the size disorder of the system increases (δ > 5%), and the average radius of the A-sites increases significantly, causing the defective fluorite structure to become highly distorted and the stress to increase sharply. To reduce the enormous stress energy generated by lattice distortion, the system spontaneously seeks a more stable atomic arrangement. Compared to defective fluorite, the perovskite structure can accommodate larger A-site ions, thus forming a two-phase coexistence structure.

[0017] 3. The high-entropy zirconate ceramic described in this invention exhibits structural stability. Due to the high-entropy effect of the system, the free energy of both the defective fluorite and perovskite phases can be reduced simultaneously, thus decreasing the free energy difference between the two phases and achieving a balanced coexistence of the two phases within a certain composition and temperature range. Simultaneously, a nanoscale alternating two-phase structure is formed. Due to the hysteresis diffusion effect, atomic migration is slow, and neither phase is prone to coarsening, resulting in a stable nanoscale, high interfacial density biphase structure.

[0018] 4. The high-entropy zirconate ceramic described in this invention is a two-phase ceramic. Compared with single-phase high-entropy ceramics, two-phase ceramics are composed of two crystals with different lattice constants, which can lead to severe mismatch at the boundaries, inducing significant stress concentration and lattice distortion. Simultaneously, the stress within the two-phase structure can also generate a large number of point defects and stacking faults. These structural changes provide new avenues for performance regulation and improvement.

[0019] 5. The high-entropy zirconate ceramics described in this invention can be applied in the fields of thermal barrier protection, thermal radiation regulation, or electromagnetic wave absorption. Attached Figure Description

[0020] The specific embodiments of the present invention will be described in further detail below with reference to the accompanying drawings.

[0021] Figure 1 This is Embodiment 1 of the present invention [La] 0.2 (Sr 0.3 Co 0.35 Ni 0.35 ) 0.8 XRD pattern of 2Zr2O7.

[0022] Figure 2 This is embodiment 2 of the present invention [La] 0.1 (Mg 0.4 Fe 0.2 Cr 0.2 Mn 0.2 ) 0.9 XRD pattern of 2Zr2O7.

[0023] Figure 3 This is embodiment 2 of the present invention [La] 0.1 (Mg 0.4 Fe 0.2 Cr 0.2 Mn 0.2 ) 0.9 HRTEM image of 2Zr2O7.

[0024] Figure 4 This is embodiment 3 of the present invention [La] 0.35 (Ca 0.42 Fe 0.29 Cr 0.29 ) 0.65XRD pattern of 2Zr2O7.

[0025] Figure 5 This is embodiment 3 of the present invention [La] 0.35 (Ca 0.42 Fe 0.29 Cr 0.29 ) 0.65 SAED diagram of 2Zr2O7. Detailed Implementation

[0026] A La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramic, the general chemical formula of which is [La] x (A y B 1-y ) 1-x ]2Zr2O7, wherein the A-site element is selected from one of Ca, Mg, and Sr, and the B-site element is selected from two or more of Fe, Cr, Mn, Co, and Ni, and the elements at the B-site are composed in an equimolar ratio; x is the molar percentage of La element in the total molar amount of La and (A+B) sites, and 0 < x < 0.4; y is the molar percentage of A element in the total molar amount of (A+B) sites, and 0.3 ≤ y < 0.5; the high-entropy zirconate ceramic has a two-phase structure of in-situ coexisting defective fluorite and perovskite, and belongs to the cubic crystal system.

[0027] Among them: the configurational entropy S of high-entropy zirconate ceramics config >1.5R, where R is the gas constant; its size disorder δ>5%.

[0028] In the formula: δ is the size disorder factor; x i for i Element molar percentage (%) n The number of element types; r i for i The ionic radius of an element; This is the weighted average of the ionic radii of the elements.

[0029] A method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics includes the following steps: (1) Weigh the raw materials according to the stoichiometric ratio, wherein the La element is derived from La2O3 oxide, the Zr element is derived from ZrO2 oxide, the A-site element is selected from one of CaO, MgO, and SrO, and the B-site element is selected from two or more oxides of Fe2O3, Cr2O3, Mn3O4, Co3O4, and NiO.

[0030] (2) Place the raw material from step (1) into a planetary ball mill. The milling media are zirconia balls, with a mass ratio (g / g) of 1-3 mm diameter zirconia balls to 5-10 mm diameter zirconia balls of 6:4. The milling solvent is deionized water. The milling speed is 300-600 r / min, and the milling time is 12-24 hours. The mass ratio (g / g / g) of balls, material, and solvent is (3-5):1:(1-2). After milling, place the mixture in a vacuum oven and dry it at 60-80℃ for 6-12 hours. After passing through a 100-200 mesh sieve, a uniformly mixed precursor powder is obtained.

[0031] (3) The precursor powder is placed in a high-temperature box furnace and calcined at high temperature in an air atmosphere at 1500~1600℃. The programmed temperature rise is as follows: the temperature is increased to 1200℃ at a rate of 5~10℃ / min and calcined for 4~6 hours; then the temperature is increased to the target temperature at a rate of 2~5℃ / min and calcined for 12~24 hours. Continuous cooling or isothermal cooling is then used, with air as the cooling medium. Finally, the mixture is ground to obtain the high-entropy zirconate ceramic.

[0032] In Examples 1-3 below, an EMPYREAN X-ray single-crystal diffractometer manufactured by Panaco GmbH (Netherlands) was used to determine the crystal structure of high-entropy zirconate ceramics. A TF20 field emission transmission electron microscope manufactured by FEI GmbH (USA) was used for microscopic morphology analysis of the high-entropy ceramics.

[0033] Example 1 A method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics includes the following steps: (1) Weigh 3.26g La2O3, 2.49g SrO, 2.24g Co3O4, 1.87g NiO and 12.32g ZrO2 to obtain raw material powder.

[0034] (2) Place the raw material from step (1) into a planetary ball mill. The milling media are zirconia balls, with a mass ratio (g / g) of 1-3 mm diameter zirconia balls to 5-10 mm diameter zirconia balls of 6:4. The milling solvent is deionized water. The milling speed is 300 r / min, and the milling time is 16 hours. The mass ratio (g / g / g) of balls, material, and solvent is 5:1:2. After milling, the mixture is placed in a vacuum oven and dried at 70℃ for 6 hours. After passing through a 200-mesh sieve, a uniformly mixed precursor powder is obtained.

[0035] (3) The precursor powder was placed in a high-temperature box furnace and calcined in an air atmosphere at 1500℃. The programmed temperature rise was as follows: the temperature was increased to 1200℃ at a rate of 8℃ / min and calcined for 6 hours; then increased to 1500℃ at a rate of 5℃ / min and calcined for 16 hours. Continuous cooling was then performed using air as the cooling medium. Finally, the powder was ground to obtain [La]. 0.2 (Sr 0.3 Co 0.35 Ni 0.35 ) 0.8 ]2Zr2O7 high-entropy zirconate ceramics.

[0036] Regarding the obtained [La] 0.2 (Sr 0.3 Co 0.35 Ni 0.35 ) 0.8 XRD tests were performed on the high-entropy ceramic powder material [2Zr2O7], and the results are as follows: Figure 1 As shown, the spectral line is in excellent agreement with the spectral lines of defective fluorite-type structure (PDF#49-1642) and perovskite-type structure (PDF#54-008) in the ICDD database, indicating that the high-entropy zirconate ceramic prepared in this embodiment has an in-situ coexistence of defective fluorite and perovskite two-phase structure.

[0037] Example 2 A method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics includes the following steps: (1) Weigh 1.63g La2O3, 1.44g MgO, 1.44g Fe2O3, 1.37g Cr2O3, 1.37g Mn3O4, and 12.32g ZrO2 to obtain raw material powder.

[0038] (2) Place the raw material from step (1) into a planetary ball mill. The milling media are zirconia balls, with a mass ratio (g / g) of 1-3 mm diameter zirconia balls to 5-10 mm diameter zirconia balls of 6:4. The milling solvent is deionized water. The milling speed is 400 r / min, and the milling time is 12 hours. The mass ratio (g / g / g) of balls, material, and solvent is 3:1:1.5. After milling, the mixture is placed in a vacuum oven and dried at 80℃ for 12 hours. After passing through a 100-mesh sieve, a uniformly mixed precursor powder is obtained.

[0039] (3) The precursor powder was placed in a high-temperature box furnace and calcined in an air atmosphere at a temperature of 1560℃. The programmed temperature rise was as follows: the temperature was increased to 1200℃ at a rate of 5℃ / min and calcined for 4 hours; then increased to 1560℃ at a rate of 3℃ / min and calcined for 24 hours. Continuous cooling was then performed using air as the cooling medium. Finally, the powder was ground to obtain [La].0.1 (Mg 0.4 Fe 0.2 Cr 0.2 Mn 0.2 ) 0.9 ]2Zr2O7 high-entropy zirconate ceramics.

[0040] Regarding the obtained [La] 0.1 (Mg 0.4 Fe 0.2 Cr 0.2 Mn 0.2 ) 0.9 XRD tests were performed on the high-entropy ceramic powder material [2Zr2O7], and the results are as follows: Figure 2 As shown, the spectrum closely matches the spectrum of defective fluorite-type structure (PDF#49-1642) and perovskite-type structure (PDF#54-008) in the ICDD database, indicating that the high-entropy zirconate ceramic prepared in this embodiment has an in-situ coexistence of defective fluorite and perovskite two-phase structure.

[0041] Regarding the obtained [La] 0.1 (Mg 0.4 Fe 0.2 Cr 0.2 Mn 0.2 ) 0.9 The high-entropy ceramic powder material of Zr2O7 was characterized by transmission electron microscopy, and the results are as follows: Figure 3 As shown, high-resolution analysis reveals the coexistence of defective fluorite (111) crystal planes (d=0.292nm) and perovskite (110) crystal planes (d=0.373nm), further demonstrating that the high-entropy zirconate ceramics prepared in this embodiment exhibit an in-situ coexistence of defective fluorite and perovskite dual-phase structure under La doping.

[0042] Example 3 A method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics includes the following steps: (1) Weigh 5.7g La2O3, 1.53g CaO, 1.50g Fe2O3, 1.43g Cr2O3 and 12.32g ZrO2 to obtain raw material powder.

[0043] (2) Place the raw material from step (1) into a planetary ball mill. The milling media are zirconia balls, with a mass ratio (g / g) of 1-3 mm diameter zirconia balls to 5-10 mm diameter zirconia balls of 6:4. The milling solvent is deionized water. The milling speed is 600 r / min, and the milling time is 24 hours. The mass ratio (g / g / g) of balls, material, and solvent is 4:1:1. After milling, the mixture is placed in a vacuum oven and dried at 60℃ for 8 hours. After passing through a 140-mesh sieve, a uniformly mixed precursor powder is obtained.

[0044] (3) The precursor powder was placed in a high-temperature box furnace and calcined in an air atmosphere at 1600℃. The programmed temperature rise was as follows: the temperature was increased to 1200℃ at a rate of 10℃ / min and calcined for 5 hours; then increased to 1600℃ at a rate of 2℃ / min and calcined for 12 hours. Continuous cooling was then performed using air as the cooling medium. Finally, the powder was ground to obtain [La]. 0.35 (Ca 0.42 Fe 0.29 Cr 0.29 ) 0.65 ]2Zr2O7 high-entropy zirconate ceramics.

[0045] Regarding the obtained [La] 0.35 (Ca 0.42 Fe 0.29 Cr 0.29 ) 0.65 XRD tests were performed on the high-entropy ceramic powder material [2Zr2O7], and the results are as follows: Figure 4 As shown, the spectrum closely matches the spectrum of defective fluorite-type structure (PDF#49-1642) and perovskite-type structure (PDF#54-008) in the ICDD database, indicating that the high-entropy zirconate ceramic prepared in this embodiment has an in-situ coexistence of defective fluorite and perovskite two-phase structure.

[0046] Regarding the obtained [La] 0.35 (Ca 0.42 Fe 0.29 Cr 0.29 ) 0.65 The high-entropy ceramic powder material of Zr2O7 was characterized by transmission electron microscopy, and the results are as follows: Figure 5 As shown, the (112) and (004) diffraction rings of defective fluorite and (200) and (220) diffraction rings of perovskite can be observed from the selected area electron diffraction image, further indicating that the high-entropy zirconate ceramic prepared in this embodiment has an in-situ coexistence of defective fluorite and perovskite biphase structure under La doping.

[0047] The above description only illustrates the preferred embodiments of the present invention and should not be construed as limiting the scope of the claims. The present invention is not limited to the above embodiments, and variations in its specific structure are permitted. All modifications made within the scope of the independent claims of this invention are also within the scope of protection of this invention.

Claims

1. A La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramic, characterized in that: The general chemical formula of this high-entropy zirconate ceramic is [La]. x (A y B 1-y ) 1-x ]2Zr2O7, wherein the A-site element is selected from one of Ca, Mg, and Sr, and the B-site element is selected from two or more of Fe, Cr, Mn, Co, and Ni, and the elements at the B-site are composed in an equimolar ratio; x is the molar percentage of La element in the total molar amount of La and (A+B) sites, and 0 < x < 0.4; y is the molar percentage of A element in the total molar amount of (A+B) sites, and 0.3 ≤ y < 0.5; the high-entropy zirconate ceramic has an in-situ coexisting two-phase structure of defective fluorite and perovskite, and belongs to the cubic crystal system.

2. The La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramic as described in claim 1, characterized in that: The configurational entropy S of the high-entropy zirconate ceramic config >1.5R, where R is the gas constant.

3. The La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramic as described in claim 1, characterized in that: The dimensional disorder δ of the high-entropy zirconate ceramic is greater than 5%.

4. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 1, comprising the following steps: (1) Weigh the raw materials according to the stoichiometric ratio, wherein the La element is derived from La2O3 oxide, the Zr element is derived from ZrO2 oxide, the A-site element is selected from one of CaO, MgO, and SrO, and the B-site element is selected from two or more oxides of Fe2O3, Cr2O3, Mn3O4, Co3O4, and NiO. (2) The raw material from step (1) is mixed with ball milling media and solvent and ball milled. After drying and sieving, a uniformly mixed precursor powder is obtained. (3) After the precursor powder is calcined at high temperature in air, it is cooled and ground to obtain high-entropy zirconate ceramics.

5. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 4, characterized in that: The conditions for ball milling in step (2) are as follows: a planetary ball mill is used, the ball milling media is zirconia balls, the mass ratio of zirconia balls with a diameter of 1~3mm to zirconia balls with a diameter of 5~10mm is 6:4, the ball milling solvent is deionized water, the ball milling speed is 300~600r / min, the ball milling time is 12~24 hours, and the mass ratio of balls, materials and solvent is (3~5):1:(1~2).

6. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 4, characterized in that: The drying conditions in step (2) refer to a temperature of 60~80℃ and a time of 6~12 hours.

7. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 4, characterized in that: The sieving condition in step (2) refers to using a sieve with a mesh size of 100-200.

8. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 4, characterized in that: The conditions for high-temperature calcination in step (3) are: calcination temperature of 1500~1600℃; the programmed temperature rise is: rise to 1200℃ at a heating rate of 5~10℃ / min, calcination for 4~6 hours; then rise to the target temperature at a heating rate of 2~5℃ / min, calcination time is 12~24 hours.

9. The method for preparing La-doped in-situ co-existing fluorite-perovskite high-entropy zirconate ceramics as described in claim 4, characterized in that: In step (3), the cooling method is continuous cooling or isothermal cooling, and the cooling medium is air.

Citation Information

Patent Citations

  • Spinel-perovskite double-phase high-entropy ceramic powder material and preparation method thereof

    CN117902879A

  • Spinel-corundum double-phase high-entropy ceramic powder material and preparation method thereof

    CN117902890A

  • Microstructure-controllable low-thermal-conductivity double-phase high-entropy ceramic material and preparation method thereof

    CN119118661A

  • Spinel-perovskite three-phase high-entropy ceramic powder material

    CN121248277A